Randomised positive control trial of NSAID and antimicrobial treatment for calf fever caused by pneumonia. (7th July 2017) - Mahendran, S. A.; Booth, R.; Burge, M.; Bell, N. J.
Abstract : One hundred and fifty‐four preweaning calves were followed between May and October 2015. Calves were fitted with continuous monitoring temperature probes (TempVerified FeverTag), programmed so a flashing light emitting diode (LED) light was triggered following six hours of a sustained ear canal temperature of ≥39.7°C. A total of 83 calves (61.9 per cent) developed undifferentiated fever, with a presumptive diagnosis of pneumonia through exclusion of other calf diseases. Once fever was detected, calves were randomly allocated to treatment groups. Calves in group 1 (NSAID) received 2 mg/kg flunixin meglumine (Allevinix, Merial) for three consecutive days and group 2 (antimicrobial) received 6 mg/kg gamithromycin (Zactran, Merial). If fever persisted for 72 hours after the initial treatment, calves were given further treatment (group 1 received antimicrobial and group 2 received NSAID). Calves in group 1 (NSAID) were five times more likely (P=0.002) to require a second treatment (the antimicrobial) after 72 hours to resolve the fever compared with the need to give group 2 (antimicrobial) calves a second treatment (NSAID). This demonstrates the importance of ongoing monitoring and follow‐up of calves with respiratory disease. However, of calves with fever in group 1 (NSAID), 25.7 per cent showed resolution following NSAID‐only treatment with no detrimental effect on the development of repeated fever or daily live weight gain. This suggests that NSAID alone may be a useful first‐line treatment, provided adequate attention is given to ongoing monitoring to identify those cases that require additional antimicrobial treatment.